Profiling for novel proteomics biomarkers in neurodevelopmental disorders. (February 2011) - Dudley, Ed; Hääßßler, Frank; Thome, Johannes
Protein biomarker discovery from biological fluids, such as serum, has been widely applied to disorders such as cancer and has more recently also been utilized in neuro-psychiatric disorders with relatively clear biological causes, such as Alzheimer''s disease and schizophrenia. The application of the associated technologies for the identification of protein biomarker signatures in neurodevelopmental disorders, such as autism spectrum disorder and attention deficit hyperactivity disorder, is comparatively less well established. The aim of this article is to provide an overview of the various protocols available for such analysis, discuss reports in which these techniques have been previously applied in biomarker discovery/validation in neurodevelopmental disorders, and consider the future development of this area of research.